Printers' devices in the Polish-Lithuanian Commonwealth : iconographic sources and ideological content - Kiliańczyk-Zięba, Justyna (2024)
"This book discusses the printers' devices used in Poland-Lithuania in the fifteenth and sixteenth centuries. The compositions that served to identify the products of individual printers are explored here as previously unacknowledged research material for cultural studies: they allow for the reconstruction of the mentality of contemporary printers as well as their co-workers and reading public. The book investigates relationships within early modern intellectual communities and shows that the textual and visual discourses of the printers' devices were pan-European, reflecting the networked communities of European centres of learning and commerce. It documents the broad range of the output of Polish-Lithuanian presses as well and is therefore also a study of book culture in a multinational and multilingual state, whose inheritance is poorly recognised internationally